Feasibility of serum CGRP measurement as a biomarker of chronic migraine: a critical reappraisal - Lee, Mi Ji; Lee, Sook-Yeon; Cho, Soohyun; Kang, Eun-Suk; Chung, Chin-Sang (Journal of headache and pain, 2018)
Background Calcitonin gene-related peptide (CGRP) has been reported as elevated in chronic migraine. We aimed to validate the role of interictal serum CGRP concentration in peripheral blood samples as a biomarker of chronic migraine. Methods We prospectively recruited patients with episodic and chronic migraine and normal controls (NCs) in the Samsung Medical Center between August 2015 and May 2016. Blood samples were collected interictally from antecubital veins per prespecified protocol. Serum CGRP measurement was performed in the central laboratory by a single experienced technician blinded to clinical information. Migraine subtype, headache days in the previous month, and the presence and characteristics of headache at ±2 days of measurement were evaluated at every visit. Results A total of 156 migraineurs (106 episodic and 50 chronic) and 27 NCs were recruited in this study. Compared to NCs (75.7 ± 20.07 pg/mL) and patients with episodic migraine (67.0 ± 20.70 pg/mL), patients with chronic migraine did not show an interictal elevation of serum CGRP levels (64.9 ± 15.32 pg/mL). Serum CGRP concentration was not associated with headache status (ictal vs. interictal), migraine subtype (migraine with vs. without aura), use of preventive or acute medications, and comorbid medication overuse. Higher serum CGRP concentration did not predict treatment response in patients with chronic migraine. Conclusions Serum CGRP concentration may not be a feasible biomarker for chronic migraine. Further validation is necessary before CGRP can be used in the clinical practice.